Business and transfer taxation : law principles and applications - Banggawan, Rex B. (Pasay City, Philippines : Real Excellence Publishing, 2019)
Summary: The objective of this book is to deliver business and transfer taxation t you, as a whole body of interconnected concepts, organized clear and recallable to the maximum extent possible.
PART I: 1. Introduction to consumption taxes -- 2. Consumption tax on importation -- 3. Consumption tax on sales -- 4. Excise tax on certain goods or services -- PART II: 1. Introduction to transfer taxation -- 2. Estate tax -- PART III: Documentation stamp tax -- PART IV: Tax remedies.
Keywords: BUSINESS ENTERPRISES -- TAXATION -- LAW AND LEGISLATION -- PHILIPPINES